UJI BEBERAPA KONSENTRASI EKSTRAK BIJI PINANG (Areca catechu L.) UNTUK MENGENDALIKAN HAMA ULAT JENGKAL (Chrysodeixis chalcites Esper) PADA TANAMAN KEDELAI (Glycine max L.) - Desita Salbiah; Rusli Rustam; Forti Senorita Daeli (UIR Press, 2019)
Chrysodeixis chalcites Esper is the main pests in soybean plants cultivation that can cause damage up to 90%. One of controlling was done by using areca nuts (Areca catechu L.) which has a potential as a botanical insecticide. This study aimed to obtain effective concentrations of areca nuts extract to control Chrysodeixis chalcites Esper pests on soybean plants (Glycine max L.). This research was conducted at the Laboratory of Plant Pest and Experimental Farm, Faculty of Agriculture, Riau University, Pekanbaru from August to November 2018. The study was conducted experimentally using a completely randomized design (CRD), which consisted of five treatments and four replications, namely: the concentration areca nuts extract 0 g.l-1 water, 20 g.l-1 water, 40 g.l-1 water, 60 g.l-1 water, and 80 g.l-1 water. The results showed that the concentration of 80 g.l-1 of water was an effective concentration to control Chrysodeixis chalcites pest with an initial death time of 14 hours, lethal time 50 29.25 hours after application, and total mortality of 87.50%.